2016
DOI: 10.1016/j.molcel.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM of Mitotic Checkpoint Complex-Bound APC/C Reveals Reciprocal and Conformational Regulation of Ubiquitin Ligation

Abstract: SUMMARY The Mitotic Checkpoint Complex (MCC) coordinates proper chromosome biorientation on the spindle with ubiquitination activities of CDC20-activated Anaphase-promoting complex/Cyclosome (APC/CCDC20). APC/CCDC20 and two E2s, UBE2C and UBE2S, catalyze ubiquitination through distinct architectures for linking ubiquitin (UB) to substrates and elongating polyUB chains, respectively. MCC, which contains a second molecule of CDC20, blocks APC/CCDC20–UBE2C-dependent ubiquitination of Securin and Cyclins, while di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
240
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(255 citation statements)
references
References 59 publications
(179 reference statements)
9
240
0
Order By: Relevance
“…Candidate substrates included the APC/C co-activator CDC20 that was ubiquitylated at Lys490 (Figure 2C). Modification of CDC20 at this site was implicated in spindle checkpoint silencing, a reaction that in vitro is brought about by the APC/C, UBE2S, and branched ubiquitin chains (Alfieri et al, 2016; Meyer and Rape, 2014; Reddy et al, 2007; Williamson et al, 2009; Yamaguchi et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Candidate substrates included the APC/C co-activator CDC20 that was ubiquitylated at Lys490 (Figure 2C). Modification of CDC20 at this site was implicated in spindle checkpoint silencing, a reaction that in vitro is brought about by the APC/C, UBE2S, and branched ubiquitin chains (Alfieri et al, 2016; Meyer and Rape, 2014; Reddy et al, 2007; Williamson et al, 2009; Yamaguchi et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…This domain contains binding pockets that recognize APC/C degrons, of which there are three major types: the destruction box (D box) (Glotzer et al, 1991), the KEN box (Pfleger and Kirschner, 2000) and the ABBA motif (Burton et al, 2011; Lischetti et al, 2014; Lu et al, 2014; Di Fiore et al, 2015; Diaz-Martinez et al, 2015) (Figure 1). A fourth sequence, the CRY motif, also binds the WD40 domain (Alfieri et al, 2016; Yamaguchi et al, 2016), but only a single instance (in Cdc20) has been identified to date (Reis et al, 2006). Over two decades of biochemical studies have defined the sequence preferences for each of the major degrons, and recent structural studies of these degrons bound to the APC/C explain the preferred amino acids at each position (He et al, 2013; Chang et al, 2015; Tian et al, 2012)(Figures 1, 2).…”
Section: Substrate Recognition By the Apc/cmentioning
confidence: 99%
“…Inhibitory proteins and phosphorylation state modulate the activity of specific APC/C isoforms and thereby govern substrate ordering. In early mitosis, activation of the SAC leads to specific inhibition of APC/C Cdc20 by the MCC, which contains multiple sequence motifs that block the degron-binding sites on Cdc20 (Alfieri et al, 2016; Yamaguchi et al, 2016). Some mammalian substrates, such as cyclin A, are degraded in the presence of the MCC, suggesting that resistance to the SAC determines the ordering of these early substrates.…”
Section: Substrate Ordering By the Apc/cmentioning
confidence: 99%
“…Our biochemical analysis of the APC/C-MCC interaction did not identify the molecular mechanisms behind this synergy but our results do not support increased levels of the MCC on the APC/C as the cause. The recently elucidated structures of APC/C-MCC complexes reveal that the MCC can block UBE2C binding when the MCC is in a closed conformation and that removal of APC15 results in a higher proportion of MCC in this closed conformation (Alfieri et al, 2016; Yamaguchi et al, 2016). One possible explanation for the observed synergy between APC15 depletion and the lack of UBE2C is that APC15 removal, through the MCC, interferes with the binding of the remaining initiating E2 enzyme UBE2D.…”
Section: Discussionmentioning
confidence: 99%
“…The MCC is composed of Cdc20 bound to the checkpoint protein Mad2 and the checkpoint complex BubR1-Bub3, and this complex can bind stably to the APC/C complex that is already bound to Cdc20 (Chao et al, 2012; Hein and Nilsson, 2014; Herzog et al, 2009; Izawa and Pines, 2014; Sudakin et al, 2001). The MCC binds to the central cavity of the APC/C and makes contact with the APC11/APC2 module and blocks UBE2C binding (Alfieri et al, 2016; Chang et al, 2014; Herzog et al, 2009; Yamaguchi et al, 2016). When all kinetochores have properly attached, the MCC needs to be disassembled in order to activate APC/C-Cdc20 and this is an active process.…”
Section: Introductionmentioning
confidence: 99%